Andean uplift patterns in the Ecuadorian Andes - Hernandez Chaparro, Daniel Ricardo (2023)
Reconstructing the exhumation history of accretionary orogens is essential for understanding the mechanisms and rates that govern subduction orogenesis. The Ecuadorian Andes constitute a bivergent orogen with active thrusting at the western flank of the Western Cordillera and in the sub-Andean ranges, at the eastern flank of the Eastern Cordillera (Cordillera Real). In the frontal Andean margin of northeastern Ecuador, Paleozoic and Jurassic to Miocene strata and positive tectonic inversion Jurassic magmatic arc rocks are exposed in a broad anticlinal named the Napo Uplift, which has been associated with transpressional deformation and ensuing positive tectonic inversion from temperatures < ~100°C. Scarce thermochronometry but abundant sedimentary provenance data indicate that exhumation in the Cordillera Real may have occurred since the Late Cretaceous, concomitant to flexural subsidence and foreland basin development farther to the east, in the present-day Napo Uplift. However, the patterns of subsequent exhumation that led to its present-day configuration remain elusive due to the lack of low-temperature thermochronometry. In this study, we conducted new apatite (U-Th)/He and fission-track analyses on Jurassic to Miocene magmatic and sedimentary rocks, as well as vitrinite reflectance in Cretaceous mudstones, from the Napo Uplift. One-dimensional thermal modeling, both single- and multi-sample, of new and published data reveals distinct periods of rapid cooling and exhumation from different morphotectonic domains in the Northern Sub-Andean Zone. We document Miocene exhumation associated with out-of-sequence thrusting across the Ecuadorian Subandean zone and document along-strike variations and possible triggering mechanisms. In the Napo uplift, we identify an uplift, commencing around ~11 Ma in the northern part and ~13 Ma in the southern region, respectively. In addition, we characterized provenance patterns using detrital apatites, integrating fission-track data, U-Pb ages, and trace element geochemistry. Our results and available multi-method proxies allow for documenting the spatial and temporal patterns of source area evolution as well as the unroofing patterns of the Cordillera Real. Altogether, our combined dataset show that the tectonic history of Napo Uplift region includes fault reactivation at ~13 Ma and thrust belt advancement after ~7 Ma most likely dominated by transpression transmitted along the deep dextral Puná-Pallatanga-Cosanga-Chingual fault system.